2019
DOI: 10.1590/1980-0037.2019v21e58684
|View full text |Cite
|
Sign up to set email alerts
|

Social support, self-efficacy and level of physical activity of students aged 13-15 years

Abstract: The aim of this study was to verify the relationship, the population attributable fraction (PAF) and the relative risk reduction (RRR) of social support and self-efficacy with level of physical activity in students. Probabilistic cross-sectional study with 1,472 students aged 13-15 years. Gender, age, social support from parents and friends, self-efficacy and levels of physical activity were evaluated through questionnaires. Data analysis was performed using Poisson regression with robust variance, PAF and RRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In contrast, considering the specific stressors of this course, this phase of the course, and even of this profession, it is understood that students have overcome the challenges at the expense of the resources they have to face them, denoting nuances of a resilient profile for this phase of the life cycle. However, it can be observed that nursing students could benefit even more from a more qualified support network, given its consequences in self-efficacy, as well as its protective role in mental health and in the coping with adversities (5)(6)(7)(9)(10)(11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, considering the specific stressors of this course, this phase of the course, and even of this profession, it is understood that students have overcome the challenges at the expense of the resources they have to face them, denoting nuances of a resilient profile for this phase of the life cycle. However, it can be observed that nursing students could benefit even more from a more qualified support network, given its consequences in self-efficacy, as well as its protective role in mental health and in the coping with adversities (5)(6)(7)(9)(10)(11) .…”
Section: Discussionmentioning
confidence: 99%
“…Student support networks are of great importance for the management of stressful situations, both in the transition period and in academic adaptation, and the lack of supporters can contribute to worse time management and less planning and organization of studies, involving issues related to autonomy, self-regulation, academic motivation, and success at the end of the first year (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in that specific time of youth, family support, and even teacher support, may have less impact than peer support on adolescent PA levels. Furthermore, in a study by Campos et al [ 18 ], social support was associated (among other variables) with levels of PA that indicated that the absence of high support from parents and friends might reduce the level of PA in adolescents. A study by Bokhorst et al [ 16 ] showed that parents and friends were perceived to be equally supportive, and friends support exceeded parental support only for ages 16–18 years.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that parental support of school learners in PA participation also contributes to maintaining PA participation habits (Tremblay et al 2015). It is important to note that a lack of family and friend encouragement decreases PA participation at the adolescent stage (Campos et al 2019).…”
Section: Introductionmentioning
confidence: 99%